P.048 Characterization of somatic mutations in mTOR pathway genes in focal cortical dysplasias. (5th June 2019) - Krochmalnek, E; Accogli, A; St-Onge, J; Addour, N; Dudley, R; Myers, K; Dubeau, F; Karamchandani, J; Farmer, J; Atkinson, J; Hall, J; Poulin, C; et al.
Abstract : Background: Focal cortical dysplasias (FCDs) are congenital structural abnormalities of the brain, and represent the most common cause of medication-resistant focal epilepsy in children and adults. Recent studies have shown that somatic mutations (i.e. mutations arising in the embryo) in mTOR pathway genes underlie some FCD cases. Specific therapies targeting the mTOR pathway are available. However, testing for somatic mTOR pathway mutations in FCD tissue is not performed on a clinical basis, and the contribution of such mutations to the pathogenesis of FCD remains unknown.Aim: To investigate the feasibility of screening for somatic mutations in resected FCD tissue and determine the proportion and spatial distribution of FCDs which are due to low-level somatic mTOR pathway mutations.Methods: We performed ultra-deep sequencing of 13 mTOR pathway genes using a custom HaloPlexHS target enrichment kit (Agilent Technologies) in 16 resected histologically-confirmed FCD specimens.Results: We identified causal variants in 62.5% (10/16) of patients at an alternate allele frequency of 0.75–33.7%. The spatial mutation frequency correlated with the FCD lesion's size and severity.Conclusions: Screening FCD tissue using a custom panel results in a high yield, and should be considered clinically given the important potential implications regarding surgical resection, medical management and genetic counselling.